THE ROLE OF COORPORATE SOSIAL RESPONSIBILITY DISCLOSURE ON FINANCIAL PERFORMANCE OF INDONESIAN ISLAMIC BANKING - Mutmainah Juniawati; Nur Hidayah (istinbath, 2020)
Islamic banking is committed to using Islamic ethical values. This certainly raises the question, whether Islamic banking that is committed to Islamic ethical values also has a high commitment to social and environmental responsibility called Corporate Social Responsibility (CSR, called social responsibility). The purpose of this study was to determine the effect of partial and simultaneous CSR disclosure on CAR, ROA, ROE, and BOPO. Based on the purposive sampling method, the sample in this study was 4 BUS and 7 UUS which published sustainability reports using GRI guidelines 4 and annual reports in 2014-2017. The analytical method used in this study is multiple linear regression. The results of this study indicate that this study shows a positive effect on CAR, because the disclosure of high CSR will increase investor loyalty and trust to invest. CSR social indicators are not needed on CAR, because it takes a long time to see their effects. All CSR indicators also do not approve of ROA and ROE. The company’s ROA and ROE are issued at the end of the year, while CSR is issued at the beginning of the following year at the AGM. CSR economic indicators show a negative effect on BOPO, because they will save resources so they will reduce their operational costs, social indicators have a positive effect on BOPO because the higher the social activities will increase the operational costs incurred